Systematic Review and Meta-Analysis of Diabetes Knowledge among Type 2 Diabetes Patients in Southeast Asia (The Review of Diabetic Studies, 2021)
OBJECTIVE: Recognition of patient baseline knowledge is important in educating patients with type 2 diabetes mellitus (T2D) to manage their disease effectively. The purpose of this study is to review current evidence on the level of diabetes knowledge among T2D patients and determine factors affecting their knowledge. METHODS: A systematic search of English language articles published between 1990 and June 2019 was conducted using six electronic databases. Only quantitative studies that assessed knowledge of T2D patients in Southeast Asian countries were included. Data were extracted and a meta-analysis was conducted. RESULTS: A total of 6210 articles were retrieved; seven articles met the inclusion criteria, comprising 1,749 T2D patients. The calculated mean knowledge score was 55.6% (95% CI: 7.6 to 103.6). Five types of assessment tools were identified ranging from five to 41 questions that focused on disease specifics, treatment, and nutrition. Age, education level, and glycemic control were the most common factors impacting knowledge. CONCLUSIONS: The level of knowledge among T2D patients in Southeast Asia was unsatisfactory, especially in older patients with low education levels and poor glycemic control. Hence, an appropriate educational plan should be prioritized to these groups.